2015
DOI: 10.2147/ndt.s78830
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography reveals lower regional blood perfusion and atrophy of the temporoparietal network associated with memory deficits and hippocampal volume reduction in mild cognitive impairment due to Alzheimer’s disease

Abstract: BackgroundAn increased electroencephalographic (EEG) upper/lower alpha power ratio has been associated with less regional blood perfusion, atrophy of the temporoparietal region of the brain, and reduction of hippocampal volume in subjects affected by mild cognitive impairment due to Alzheimer’s disease as compared with subjects who do not develop the disease. Moreover, EEG theta frequency activity is quite different in these groups. This study investigated the correlation between biomarkers and memory performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Our findings, with 57% of patients (who had an EEG) with either non-specific or encephalopathic alterations are in accordance with previous findings 35 . Brain electrical activity is coupled with perfusion, and EEG alterations have been associated with hypoperfusion in Alzheimer's disease 36 . Interestingly, in COVID-19, EEG modifications are more frequent in the frontal regions 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, with 57% of patients (who had an EEG) with either non-specific or encephalopathic alterations are in accordance with previous findings 35 . Brain electrical activity is coupled with perfusion, and EEG alterations have been associated with hypoperfusion in Alzheimer's disease 36 . Interestingly, in COVID-19, EEG modifications are more frequent in the frontal regions 37 .…”
Section: Discussionmentioning
confidence: 99%
“… Vecchio et al (2014) discovered that MCI subjects were significantly impaired in theta but not alpha bands connectivity compared with normal aging with graph theoretical analysis. A study of EEG revealed that upper/low alpha power ratio could predict MCI, which was associated with cortical thinning and less perfusion in the temporoparietal area ( Moretti, 2015 ).…”
Section: Aging and Mild Cognitive Impairment-related Changes Of Brainmentioning
confidence: 99%
“…Not surprisingly, in case of PGRN deficiency, the high alpha frequency spectral power increments. The alpha oscillation is the rhythm that mirrors the brain electrical signal of the parietal-occipital default system, profoundly connoted with higher cognitive abilities ( Klimesch, 2012 ; Moretti, 2015a ). Recent studies have shown that mutations in GRN are correlated with atrophy of the parietal lobes ( Pickering-Brown et al, 2008 ; Seeley, 2008 ; Van Swieten and Heutink, 2008 ).…”
Section: Discussionmentioning
confidence: 99%